2016
DOI: 10.1152/ajpregu.00366.2015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological evidence for low-abundance TRPV3 expression in primary vagal afferent neurons

Abstract: Primary vagal afferent neurons express a multitude of thermosensitive ion channels. Within this family of ion channels, the heat-sensitive capsaicin receptor (TRPV1) greatly influences vagal afferent signaling by determining the threshold for action-potential initiation at the peripheral endings, while controlling temperature-sensitive forms of glutamate release at central vagal terminals. Genetic deletion of TRPV1 does not completely eliminate these temperature-dependent effects, suggesting involvement of add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In a recent study using fluorescent calcium imaging on dissociated TRPV3 KO mouse vagal afferent neurons, we observed that EVA still activated many neurons (Wu et al, 2016), even though TRPV3 is the only reported target of EVA (Xu et al, 2006). This suggested the presence of an additional calcium influx pathway stimulated by EVA.…”
Section: Eva and Aitc Activation Overlaps In Vagal Afferents And Trpamentioning
confidence: 77%
See 4 more Smart Citations
“…In a recent study using fluorescent calcium imaging on dissociated TRPV3 KO mouse vagal afferent neurons, we observed that EVA still activated many neurons (Wu et al, 2016), even though TRPV3 is the only reported target of EVA (Xu et al, 2006). This suggested the presence of an additional calcium influx pathway stimulated by EVA.…”
Section: Eva and Aitc Activation Overlaps In Vagal Afferents And Trpamentioning
confidence: 77%
“…We had originally overlooked the importance of TRPA1 in vagal afferent neurons, turning our attention toward TRP channels stimulated by warm temperatures such as TRPV3. However, EVA also stimulated a significant number of vagal afferent neurons in TRPV3 KO mice, demonstrating that EVA is not a selective TRPV3 agonist (Wu et al, 2016). Using a more selective TRPV3 agonist (farnesyl pyrophosphate), we pharmacologically determined that TRPV3 was present in vagal afferent neurons in extremely small amounts (Wu et al, 2016), and therefore was likely negligible to the overall EVA response observed in wild-type animals.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations